Development of interactive guide to Krakow - Федько, Юлия Игоревна (Eastern-European Journal of Enterprise Technologies, 2012)
The design and development of information structure, exterior design of the electronic publication, as well as the creation of navigation are described in this paper. The choice of colors and fonts, hardware and software is proved